Mental Health Outcomes in Healthcare Workers in COVID-19 and Non-COVID-19 Care Units: A Cross-Sectional Survey in Belgium - Tiete, Julien; Guatteri, Magda; Lachaux, Audrey; Matossian, Araxie; Hougardy, Jean-Michel; Loas, Gwenolé; Rotsaert, Marianne (Frontiers in Psychology, 2021)
Background: Literature shows negative psychological impact of the COVID-19 outbreak on frontline healthcare workers. However, few is known about physicians’ and nurses’ mental health, working in general hospitals during the outbreak, caring for patients with COVID-19 or not. Objectives: This survey assessed differences in mental health in physicians and nurses working in COVID-19 or non-COVID-19 medical care units. Design: A cross-sectional mixed-mode survey was used to assess burnout, insomnia, depression, anxiety, and stress. Setting: 1244 physicians and nurses from 5 general hospitals in Belgium, working in COVID-19 care units (CCU), non-COVID-19 care units (NCCU) or both (CCU+NCCU) were informed of the study. Participants: 647 healthcare workers participated in the survey (response rate = 52%). Measurements: Validated instruments were used to assess the primary outcomes: the PFI (burnout/professional fulfillment), the ISI (insomnia), and the DASS-21 (emotional distressdepression, anxiety, and stress). Results: Results showed high prevalence of burnout, insomnia, and emotional distress depression, and anxiety among participants. After adjusting for confounders, multivariate analysis of variance showed no differences between CCU, NCCU and CCU+NCCU workers. Univariate general linear models showed higher level of burnout, insomnia and anxiety among nurses in comparison to physicians. Being a nurse, young, isolated, with an increased workload were risk factors for worse mental health outcomes. Limitations: The mental health of the tested sample, before the outbreak, is unknown. Moreover, this cross-sectional design provides no information on the evolution of the mental health outcomes over time. Conclusions: Directly caring for patients with COVID-19 does not worsen is not associated with worse mental health outcomes among healthcare workers in general hospitals. High prevalence of burnout, insomnia, and emotional distressdepression and anxiety among physicians and nurses requires special attention and specific interventions need to be implemented. Protocol Registration: NCT04344145 Funding: No funding supported this study.